Analysis of Fintech Payments on Consumer Behavior of Digital Business Students - Ilham, Ratih Milati; Ainiyah, Erika Rodhotul; Nafiah, Virda Saidatun (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
This study aims to analyze whether there is an influence of Fintech Payment on Consumptive Behavior. The population in this study were all students of the Digital Business FEB UPGRIS. The number of samples in this study was 66 students. The sampling technique used the purposive sampling method. The research method used is quantitative with data sources in the form of primary data. The data analysis method uses simple linear regression analysis with SPSS version 25. The results of this study provide evidence that the Fintech Payment variable can influence the consumptive behavior of students of the Digital Business Study Program, FEB UPGRIS.